Отношения между родителями и детьми с нарушениями слуха - Namazbayeva, Zh; Daurambekova, A (Journal of Educational Sciences, 2019)
The article describes the potential and possibilities of applying theatrical pedagogy for the formation of children with disabilities in the development of social and communication skills. The authors analyze the physiological and psychological features of children with hearing disorders, children with limited intellectual abilities. The purpose of the article: the search for effective ways of communication of parents with children with hearing disorders. Owing to the use of dramatized games, children’s thinking expands, game activities help children enter into conversation, develop their creative abilities. Theatrical game actions are performed by children using imitation, physical gestures and contact, speech intonation. The limited ability of hearing development can lead to insufficient development of the child’s cognitive activity and a weak manifestation of clear emotional characteristics. Children with disabilities, with hearing disorders can overcome difficulties in mastering the curriculum through the use of theatrical techniques. Teachers in this way can also provide them with psychological support and assistance in mastering their emotional and social-communicative skills. The recommendations for parents to interact with children with hearing disorders were suggested. Key words: children with intellectual disabilities, social and communication skills, theatrical play activity, creative abilities, mimicry, intonation, physical movements of children with hearing disorders.